2005
DOI: 10.1002/ijc.20756
|View full text |Cite
|
Sign up to set email alerts
|

Estimating dose‐response relationship between ethanol and risk of cancer using regression spline models

Abstract: Cancers of the upper aero-digestive tract (i.e., oral cavity, pharynx, larynx and oesophagus) are largely attributable to smoking and drinking habits, but the correct estimation of the dose-response relationship between alcohol and cancer risk is challenging.Step functions are widely used to estimate risks and to evaluate trends of continuous exposure. However, results are influenced by the selection of the reference category and cutpoints. More flexible models, like spline regression and fractional polynomial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 25 publications
4
32
0
1
Order By: Relevance
“…Consistent with previous studies (Blot et al, 1988;Boffetta and Garfinkel, 1990;Adami et al, 1992;Franceschi et al, 1994;Gronbaek et al, 1998;Kjaerheim et al, 1998;Hayes et al, 1999;Boffetta et al, 2001;Boeing, 2002;Castellsague et al, 2004;Sturgis et al, 2004;Polesel et al, 2005;Boffetta and Hashibe, 2006), predominantly of men, we observed a significant dose -response association between increasing alcohol consumption and head and neck cancer in both male and female alcohol drinkers. Results were generally similar for beer, liquor, and wine, although only 0.3% (1528) of the cohort (1064 men and 464 women) drank 43 glasses of wine per day limiting power.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies (Blot et al, 1988;Boffetta and Garfinkel, 1990;Adami et al, 1992;Franceschi et al, 1994;Gronbaek et al, 1998;Kjaerheim et al, 1998;Hayes et al, 1999;Boffetta et al, 2001;Boeing, 2002;Castellsague et al, 2004;Sturgis et al, 2004;Polesel et al, 2005;Boffetta and Hashibe, 2006), predominantly of men, we observed a significant dose -response association between increasing alcohol consumption and head and neck cancer in both male and female alcohol drinkers. Results were generally similar for beer, liquor, and wine, although only 0.3% (1528) of the cohort (1064 men and 464 women) drank 43 glasses of wine per day limiting power.…”
Section: Discussionsupporting
confidence: 92%
“…Although some previous epidemiological studies have observed a protective association between moderate alcohol consumption and cancers of the head and neck and the aesophagus, results overall have been inconsistent (Franceschi et al, 1994;Gronbaek et al, 1998;Hayes et al, 1999;Castellsague et al, 2004;Polesel et al, 2005). Most previous studies were conducted in populations that drink larger amounts of alcohol (Altieri et al, 2005) than that of the current study.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…California law requires cancer case information to be reported to the California Cancer Registry [4]. The recruitment method was by regular oral cancer screening and by obtaining patient consent.…”
Section: Samplingmentioning
confidence: 99%